Humanitarian news frame in Harian Republika and Kompas on Wamena ferugees (framing analysis on Republika news and Kompas edition 24 - 30 September 2019 on the tragedy of the riots in Wamena) - Sitohan, Ghafur (Universitas Ahmad Dahlan, 2021)
Conflict against the backdrop of the dissemination of hoaks information, accompanied by elements of racism repeated and targeted papuans. In 2019, a riot led to an alleged racist slur by a teacher, to his student on September 18, 2019. The unrest resulted in various humanitarian problems, such as civilian casualties and destruction of public facilities. As a result, a wave of problems related to the exodus of citizens continues to come. This research aims to discuss the news frame of two media, namely Republika Daily and Kompas with discussion of the Tragedy of Riots in Wamena City, Papua Province (September 24, 2019 - September 30, 2019). Meanwhile, the concept of a crisis of manness and responsibility to protect both media, agreed to package it in the same point of view. The frame of republika and kompas daily news in the concept of humanitarian crisis is classified in the complex emergencies category, and the facts presented about the role of the Government in accordance with the concept of responsibility to protect.